Recent advances in the transition-metal catalyzed synthesis of multisubstituted pentenolides and related pyranones - Špulák, Marcel; Ghavre, Mukund; Pour, Milan (Tetrahedron letters, 2017)
[Display omitted] •Recent metal-catalyzed syntheses of substituted pentenolides and related pyranones reviewed.•Brief discussion of the strategies included.•Emphasis placed on homogeneous catalysis. This digest focuses on the transition-metal catalyzed syntheses of variously substituted pentenolides, published recently. The review is based on methodologies for the synthesis of pentenolides rather than isolated examples, and covers post-2007 publications reported on this subject. Brief discussion of the strategies, strengths and drawbacks of the syntheses is also included.